Effects of digestates from different biogas production systems on above and belowground grass growth and the nitrogen status of the plant‐soil‐system. (10th October 2013) - Andruschkewitsch, Meike; Wachendorf, Christine; Wachendorf, Michael
Abstract Biogas production from residual biomass (e.g. from extensively managed grassland) can help securing ecosystem services of such vegetation and may contribute to energy production from renewable resources. Proper management of fermentation residues is a major challenge within the technical concepts recently suggested for the conversion of this biomass. A 5‐month pot experiment was conducted to investigate the effects of digestates from separated grass silage (liquid fraction) (SGD), produced within the innovative integrated generation of solid fuel and biogas from biomass (IFBB) system and from conventional whole crop digestion (WCD) on grass growth, N uptake and N immobilization. Digestates and a mineral N fertilizer (MIN) as comparative variant were applied at N‐rates from 0 up to 20 g N m−2 based on fertilizer mineral N to three different grass species (Lolium perenne, Trisetum flavescens and Festuca rubra subsp. rubra). Digestate application increased harvestable biomass constantly with increasing N‐rate for L. perenne, but not for T. flavescens and F. rubra rubra. Type of digestate caused species‐specific differences in plant growth, as F. rubra rubra and L. perenne showed higher dry matter (DM) yields of harvestable and root biomass for WCD and T. flavescens for SGD application. However, for both digestates, reduced root biomasses were observed compared to the control. The mineral nitrogen use efficiency (NUEmin) was over all species 22% higher for harvestable and 33% for stubble biomass after application of SGD compared to WCD, due to greater N uptake related to lower gaseous N losses and favorable mineralization properties. N immobilization measured by soil microbial biomass N (MBN) was influenced by grass species but not by type of digestate or application rate. The lack of effect of digestate application on MBN was attributed to the compensation of the digestate carbon input by the reduced root biomass production.